The Effectiveness of SUNO AI Based English Songs to Improve Student's Vocabulary - Tri Akhsanul Amal; Muh Shofiyuddin (Institut Agama Islam Negeri Palopo, 2025)
This study investigates the effectiveness of Suno AI, an artificial intelligence-based English song learning tool, in enhancing vocabulary mastery among eighth-grade students at a junior high school in Jepara. The background of the research stems from the challenges students face in acquiring vocabulary using conventional methods. The objective of this study is to determine whether Suno AI can significantly improve students’ vocabulary acquisition. A quasi-experimental research design was employed, with an experimental class receiving instruction using Suno AI and a control class following traditional vocabulary learning methods. Pre-test and post-test data were collected and analyzed using statistical methods, including the Shapiro-Wilk test for normality, the Levene test for homogeneity, and a paired-sample T-test to assess the effectiveness of the intervention. The findings indicate a significant improvement in the vocabulary mastery of students in the experimental class compared to the control class, demonstrating that AI-powered learning tools can enhance engagement and retention. This research contributes to educational technology by highlighting the potential of AI applications in language learning, paving the way for more interactive and effective vocabulary instruction.